Ideology, History, and the Construction of "Woman" in Late Ancient Christianity - Clark, Elizabeth A. (Journal of early Christian studies, 1994)
Theorists who specialize in ideology critique have noted various ways in which ideology operates to "fix" representations of the self: through stereotyping, naturalizing, universalizing, and de-historicizing of the self. Certain types of narrative writing and intertextual writing practices also serve as carriers of ideological meaning. In this essay, the writings of the Church Fathers pertaining to women are mined to demonstrate the ideological operations that can be noted therein. The effort to "re-historicize" these writings is explored in relation to the social location of the Fathers. The essay concludes with a brief suggestion that the ideological construction of an essentialized "woman" by the Fathers was not entirely successful, being in part subverted by both the patristic authors themselves as well as by the women whose identities they attempted to "fix."